Mysticons. Volume 1 - Leth, Kate; Jara, Sean (Dark Horse Books, 2018)
"Arkayna, Zarya, Emerald, and Piper--unexpected heroes who together become epic warriors as well as the closest of friends--are drawn together by a prophecy to battle evil and protect the realm!"--